Repurposing of Dipeptidyl Peptidase-4 Inhibitors - Nulaka, Sravanthi Reddy; Nimmala, Anusha; Pasupuleti, Rakesh; Ieppala, Sripriya; Boggula, Narender; Bakshi, Vasudha; Pathakala, Naveen (Asian Journal of Pharmaceutical Research and Development, 2020)
Back ground: Anti-oxidants play an important role to protect damage caused by oxidative stress (OS). Free radical and Reactive Oxygen Species (ROS) are basically the main cause of several disorders in humans that are generated as an imbalance between formation and neutralization of pro-oxidants resulting in oxidative stress. They cause oxidative damage to lipids, proteins, and DNA, eventually leading to many chronic diseases, such as cancer, diabetes, aging and other degenerative diseases in humans. Various studies have been done to identify anti-oxidants from plant sources and efforts have been taken to incorporate it in conventional therapy. Objective: The aim of the present research work is to assess the repurposing potential of dipeptidyl peptidase-4 inhibitor by checking its anti-oxidant activity. Methods: Anti-oxidant potential of the vildagliptin was studied using different in vitro methods. The anti-oxidant activity was estimated by using DPPH radical scavenging activity, nitric oxide scavenging assay, hydrogen peroxide scavenging assay and reducing power assay methods. The ascorbic acid used as a standard reducing agent. All the analysis was made with the use of UV-Visible spectrophotometer. Results: The extract showed good dose dependent free radical scavenging property in both the models used in this study. The results of the assay showed that it possesses significant free radical scavenging and reducing power properties at concentration-dependent manner. Conclusion: This study suggests that vildagliptin exhibit great potential for anti-oxidant activity and may be useful for their medicinal functions. However, further exploration is necessary for effective use in both modern systems of medicines. This will further trigger extensive research for better understanding of the impact of vildagliptin on health.